Sending Out an SMS: Automatic Enrollment Experiments for Overdraft Alerts - GRUBB, MICHAEL D.; KELLY, DARRAGH; NIEBOER, JEROEN; OSBORNE, MATTHEW; SHAW, JONATHAN (Journal of Finance, 2025)
ABSTRACT At‐scale field experiments at major U.K. banks show that automatic enrollment into “just‐in‐time” text alerts reduces unarranged overdraft and unpaid item charges 17% to 19% and arranged overdraft charges 4% to 8%, implying annual market‐wide savings of £170 million to £240 million. Incremental benefits from “early‐warning” alerts are statistically insignificant, although economically significant effects are not ruled out. Prior to the experiments, over half of overdrafts could have been avoided by using lower‐cost liquidity available in savings and credit card accounts. Alerts help consumers achieve less than half of these potential savings.